Multiobjective grid packing model: An application in forest management - Snyder, S.; ReVelle, C. (Location science, 1997)
In this paper, we formulate and solve a 0/1 multiobjective integer programming model that addresses the management of two conflicting forest resources: wildlife habitat and timber harvesting activities, subject to certain spatial restrictions. The tradeoff between these two conflicting resource uses is addressed in the context of a regular grid of parcels for a single time period problem. Timber harvest adjacency constraints were developed and incorporated into the model which prevented harvests from occurring next to one another, as well as next to habitat areas. The model performed exceptionally well computationally with hypothetical data. The majority of runs were solved exactly in their relaxed form in less than 60 s using the multiobjective weighting method, with the remaining cases requiring only a few branch and bound nodes to solve to completion.